2007
DOI: 10.1007/bf03086004
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care platelet function testing in patients undergoing PCI: between a rock and a hard place

Abstract: Point-of-care platelet function testing in patients undergoing PCI: between a rock and a hard place Since recent studies have linked an impaired response to antiplatelet therapy with a higher incidence of atherothrombotic events, the monitoring of the efficacy of antiplatelet therapy in the individual patient has attracted much attention. In the present report, we demonstrate that platelet function testing with several point-of-care assays results in ambiguous and conflicting results: some assays indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…However, in the same study, they reported that results from two other platelet aggregation tests, PFA‐100 and platelet works, were not predictive of perioperative bleeding and transfusions . Subsequent studies have also demonstrated substantial variability and even conflicting results from different point‐of‐care platelet function assays . This suggests that individual assays must be independently validated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the same study, they reported that results from two other platelet aggregation tests, PFA‐100 and platelet works, were not predictive of perioperative bleeding and transfusions . Subsequent studies have also demonstrated substantial variability and even conflicting results from different point‐of‐care platelet function assays . This suggests that individual assays must be independently validated.…”
Section: Discussionmentioning
confidence: 99%
“…13 Subsequent studies have also demonstrated substantial variability and even conflicting results from different point-of-care platelet function assays. 17 This suggests that individual assays must be independently validated.…”
Section: Discussionmentioning
confidence: 99%
“…Usually, reference platelet count taken from the K3-EDTA anticoagulant blood without ADP and other count is taken from citrated anticoagulant sample with ADP agonist. 71 In normal patients, the platelets get aggregated in the presence of agonist and the resultant platelet count is considered to be zero.…”
Section: Plateletwork Analyzermentioning
confidence: 99%
“…72 When the platelet aggregates Minimum studies have been conducted to show the prediction of outcomes of cardiovascular diseases. 71,73,76 In the determination of the cut-off values for Plateletworks assay, it had shown 63% sensitivity and 58.5% specificity using ROC curve analysis. 74 Around 5%-40% of patients who are under clopidogrel therapy may show resistance to clopidogrel and the cause may be due to impaired drug absorption by the hepatic cells or impaired drug metabolic activity.…”
Section: Plateletwork Analyzermentioning
confidence: 99%
“…9,10 However, platelet function was measured with impedance aggregometry, a method that has not been very well studied with respect to P2Y 12 inhibition. 11 Therefore, we aimed to study the effect of cangrelor on platelet aggregation in patients pretreated with aspirin and clopidogrel using the 'gold standard' light transmittance aggregometry (LTA).…”
mentioning
confidence: 99%